Antioxidant and Anti-Inflammatory Activity of the Ethanolic Extract of Euphorbia Hirta Leaf Extract: An In Vitro and In Silico Study - Praveen G; Krishnamoorthy Kaliselvi; Veeraraghavan Vishnu Priya (Wolters Kluwer Medknow Publications, 2024)
ObjectivesThis study presents the antioxidant and anti-inflammatory activity of the ethanolic extract of Euphorbia hirta leaf extract. Materials and MethodsThe antioxidant and anti-inflammatory activity of the extract was performed by in vitro assay. Our research employs a comprehensive approach combining experimental assays and computational simulations to assess the extract's potential bioactive components and their interactions with key biomolecules. ResultsThe study's results demonstrated a progressive rise in the percentage of inhibition, which was dependent on the dosage, in both antioxidant and anti-inflammatory activities. This trend was observed for both the extract and the standard, encompassing concentrations ranging from 100 to 500 μg/ml. ConclusionThe results showed that Euphorbia hirta's possesses antioxidant and anti-inflammatory activity, and this may contribute to a traditional medicinal. The discoveries of this study contribute to a deeper understanding of Euphorbia hirta's medicinal properties and its potential as a source of natural therapeutic agents.